Resource Recycling for Enhancing Farm Productivity and Profitability in Integrated Farming System under Rainfed Situation in Odisha, India: A Recent Study - Hemanta Kumar Sahoo; Amit Phonglosa; Basudev Behera (Current Topics in Agricultural Sciences Vol. 2, 2021)
The present study was carried out in 0.8 ha rainfed farm from April 2010 to March 2013 with two sources of water i.e. no pond/rainfed and pond/irrigated in five different blocks viz., Khajuripada of Kandhamal district (North Eastern Ghats Zone), Dhenkanal Sadar and Odapada of Dhenkanal district (Mid Central Table Land Zone), Golamunda and Narla of Kalahandi district (Western Undulating Zone) of Odisha. Integrated Farming System (IFS) model farm recorded 31.92 q Rice Equivalent Yield (REY) as compared 3.78 REY in conventional rice-greengram system. The net return in IFS model was Rs. 1,61,148/- whereas an amount of Rs. 11,631/- was obtained in conventional system. The recyclable wastes of 3.3 t paddy straw, 3000 kg pond silt, 2129 kg poultry excreta and 13 t mushroom spent in IFS model were used as resources for use by different components of IFS model. The productivity and profitability of IFS models were higher due to efficient recycling of wastes. Almost no waste was left to pollute the environment or to degrade the resource base where as the wastes in conventional system were not utilized effectively.